El Sonidero de la Azotea: performance, utopía y afectos en tiempos de confinamiento - Camila Aschner Restrepo (Revista de Estudios Sociales, 2022)
The sonidero, a landmark in the Mexican festive landscape, represents both the mobile sound system and its owner and creator. This article examines the case of El Sonidero de la Azotea and the way in which it adapted to the restrictions imposed in response to the COVID-19 pandemic. It does this with a view to theorizing about the place of the utopian and the affective in contemporary physical and virtual performance.